Floristic Composition and Phytodiversity Status of Bangabandhu Jamuna Eco-Park, Sirajganj, Bangladesh - Islam, Md. Ashraful; Rahman, M. Mahfuzur; Hossain, Gazi Mosharof (International Journal of Scientific Research in Biological Sciences, 2024)
The present study represents a comprehensive information on current floristic composition and phytodiversity status of Bangabandhu Jamuna Eco-Park, Sirajganj, Bangladesh. This study reveals that a total 279 vascular plant species of 205 genera under 73 families have been documented during 2021 to 2022. From recorded species, 71 species (25.45%) were planted and 208 species (74.55%) were wild in nature. Pteridophytes are represented by six species (2.15%) under six genera (2.93%) of five families (6.85%) and Gymnosperms of two species (0.72%) under two genera (0.97%) of two families (2.73%), Angiosperms are composed of 215 species (77.06%) of 156 genera under 55 families of Magnoliopsida (dicotyledons) and 56 species (20.07%) of 41 genera under 11 families of Liliopsida (monocotyledons). Among the Angiosperm families, Asteraceae with 22 species is the largest dicotyledons family, where Poaceae with 20 species is the largest monocotyledonous family. Among the life-form categories, 85 species are erect herb and rest of 39, 31 and 22 species are represented as large tree, prostrate herb and small shrub, respectively. Seasonal variation is remarkably observed in this study, where the maximum 172 species are found during rainy season, following by 134 and 108 species are recorded during winter and summer seasons respectively. The highest values of both Shannon-Weiner diversity index (2.77) and Simpson diversity index (0.10) are found during rainy season, whereas the lowest values of these indices are calculated as 2.28 and 0.07, respectively during summer season. Similarly, the highest Jackknife species richness value 172.58 is recorded in rainy season and the lowest value 108.75 in summer season. Thus, the eco-park area is floristically quite good and which might serve as an excellent centre for biodiversity conservation by strengthening the existing management plans and adopting necessary policies and strategies.